Toxic effects of molluscicidal baits to the terrestrial isopod Porcellionides pruinosus (Brandt, 1833) - Santos, Miguel João G.; Ferreira, Nuno G. C.; Soares, Amadeu M. V. M.; Loureiro, Susana (Journal of soils and sediments, 2010)
Purpose Methiocarb and metaldehyde are the most common molluscicides applied in agricultural and horticultural fields in Portugal and elsewhere in Europe. The application of molluscicidal baits to control slug and snail populations can pose a threat to non-target organisms like terrestrial isopods, because they are detritivorous and may feed on the toxic baits applied to the soil surface. The aim of this work was to evaluate the effects and understand the modes of action of these molluscicides to terrestrial isopods. Materials and methods In this study, the terrestrial isopod Porcellionides pruinosus was exposed to these two molluscicides, and the time to lethality was evaluated. Biochemical indicators (biomarkers) are known to provide early warning signs of environmental pollution or stress conditions to the organisms, by measuring cellular or molecular responses of the target organism to xenobiotic agents. Therefore, to evaluate modes of action and effects and also to see if biomarkers can be used as early warning tools in molluscicidal exposures, three different enzymes, glutathione S -transferase (GST), acetylcholinesterase (AChE) and catalase (CAT), were analysed upon single exposures and binary mixtures tests. Results and discussion These two molluscicides showed to be of extreme concern regarding terrestrial isopods, as all animals died after 24 h of exposure to methiocarb, and only 20% survived after 56 h of exposure to metaldehyde. Results indicate that the carbamate methiocarb inhibited significantly AChE activity, but no effects were observed in CAT and GST levels. The exposure to metaldehyde had no effects on AChE, but a decrease in GST activity as well as a general increase in CAT activity was observed at the higher exposure period tested (32 h). The combined exposure of the two molluscicides resulted in a general decrease in AChE and CAT activity, but no visible effects were observed in terms of GST activity. Conclusions The LT50 values found in the single exposures to both molluscicides were very low, especially in the case of the carbamate methiocarb. The use of several biomarkers was a suitable tool to understand the mode of action of these two molluscicides in this isopod species.